2020
DOI: 10.3389/fgene.2019.01326
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the DREB Subfamily in Saccharum spontaneum Reveals Their Functional Divergence During Cold and Drought Stresses

Abstract: Drought and cold stresses are the main environmental factors that affect the yield of sugarcane, and DREB genes play very important roles in tolerance to drought, cold, and other environmental stresses. In this study, bioinformatics analysis was performed to characterize Saccharum spontaneum SsDREB genes. RNA sequencing (RNA-seq) was used to detect the expression profiles of SsDREBs induced by cold and drought stresses. According to our results, there are 110 SsDREB subfamily proteins in S. spontaneum, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 72 publications
1
21
1
Order By: Relevance
“…The identified number of DREB genes in S. tuberosum (66) is greater than that in Arabidopsis (56) which may be due to the difference in their genome sizes. When compared to previous studies, greater numbers of DREB genes were reported in S. spontaneum (110) (Huang et al, 2020), P. trichocarpa (75) (Chen et al, 2013), soybean (73) (Zhou et al, 2020), and malus (68) (Zhao et al, 2012), but less DREB genes were found in sesame (41) (Dossa et al, 2016), maize (51) (Du et al, 2014), mulberry (30) (Liu et al, 2015), grape (38) (Zhao et al, 2014), common bean (54) (Konzen et al, 2019), Phyllostachys edulis (27), and pineapple (20) (Chai et al, 2020). In order to comprehend the potential functions of proteins, it is inevitable to compute the physiochemical characteristics of plant protein families (Salih et al, 2019).…”
Section: Discussioncontrasting
confidence: 57%
“…The identified number of DREB genes in S. tuberosum (66) is greater than that in Arabidopsis (56) which may be due to the difference in their genome sizes. When compared to previous studies, greater numbers of DREB genes were reported in S. spontaneum (110) (Huang et al, 2020), P. trichocarpa (75) (Chen et al, 2013), soybean (73) (Zhou et al, 2020), and malus (68) (Zhao et al, 2012), but less DREB genes were found in sesame (41) (Dossa et al, 2016), maize (51) (Du et al, 2014), mulberry (30) (Liu et al, 2015), grape (38) (Zhao et al, 2014), common bean (54) (Konzen et al, 2019), Phyllostachys edulis (27), and pineapple (20) (Chai et al, 2020). In order to comprehend the potential functions of proteins, it is inevitable to compute the physiochemical characteristics of plant protein families (Salih et al, 2019).…”
Section: Discussioncontrasting
confidence: 57%
“…Only in 2018, modern technologies enabled the assembly of a chromosome- and allele-level genome of an Ssp clone ( Zhang et al, 2018 ). This study paved the way for several comprehensive analyses of gene families in the species ( Hu et al, 2018 ; Shi et al, 2019 ; Wang et al, 2019a , b , c ; Zhang et al, 2019b ; Huang et al, 2020 ; Li et al, 2020 ; Su et al, 2020a ). Here, we analyzed the kinome of not only sugarcane but also sorghum, a close diploid relative.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the RAV group of the AP2/ERF family also have important functions in plant hormone signal transduction and the regulation of responses to biotic and abiotic stimuli [26,27]. Dehydration-responsive element-binding (DREB) members, as important plant-specific transcription factor, also belong to the AP2/ERF superfamily and are involved in response to abiotic stresses [28]. Furthermore, various studies have reported the involvement of DREBs and other ERF members in dealing with water deficit [29,30], cold, and oxidative [31] and salinity [32,33] stresses.…”
Section: Introductionmentioning
confidence: 99%